CURRICULUM CONCEPT AT THE LEVEL OF EDUCATION UNIT - Aidil Saputra (Jurnal Ilmiah Teunuleh, 2021)
The education unit level curriculum (KTSP) is the latest curriculum in Indonesia that is recommended to be used as a reference by curriculum developers at the education unit level. KTSP is a curriculum oriented towards the achievement of co-existence, therefore this curriculum is an improvement of the curriculum based on co-existence. The Education Unit Level Curriculum (KTSP) which was implemented gradually starting in 2006 gives teachers and schools (Educational Unit Level Institutions) the flexibility to develop it. Teachers and schools are given the freedom to create by relying on content standards, graduation standards, and curriculum preparation guidelines set by the government (c.q. National Standards Agency for Education). Curriculum Level Education Unit, born from the spirit of regional autonomy, where education affairs are not all central responsibility, but partly the responsibility of the region, therefore judging by the pattern or model of development KTSP is one of the models of curriculum that is desentralistic. The nature of KTSP itself includes the understanding, purpose, basis or foundation of development, principles of development and components of KTSP.